FORMULASI DAN UJI SEDIAAN PEMBERSIH TANGAN ANTISEPTIK DENGAN EKSTRAK JERUK NIPIS TERHADAP BAKTERI SALMONELLA TYPHI - Lukky Jayadi; Sandry Kesuma; Muhammad Hasan Wattiheluw (JCPS (Journal of Current Pharmaceutical Sciences), 2022)
Infectious diseases are still common in the environment in Indonesia. For example, microorganisms that cause problems enter the human body through the hands. Many microorganisms stick to human hands which then enter the human body with food that enters the human mouth. The busyness and density of human work that requires the development of health sciences in adjusting behavior such as the use of sterile antiseptics. This study aims to see the effectiveness of antiseptic hand sanitizers that can kill bacteria made from alcohol and lime extract against Salmonella typhi microbes. The test strategy for examination in this study was to see the ability to kill microbes or eliminate microorganisms from antiseptic hand sanitizer preparations after 30 and 60 seconds with the AOAC 960.09 technique. The results showed that it could reduce or kill Salmonella typhi microbes equivalent to 99.9% after 30 and 60 seconds. In this review, the pH of the antiseptic hand sanitizer of lime extract was obtained the pH was 4 and for the determination of the specific gravity the specific gravity was 0.9669 g/ml. From the discussion of the research, it is illustrated that there is a relationship between the composition of antiseptic hand sanitizer preparations with alcohol content with the addition of lime extract to a slightly acidic pH, specific gravity according to liquid preparations in general and the excellent reducing or killing power of bacteria from these preparations. Keywords: Antiseptic Hand Sanitizer Preparations, Lime, Salmonella typhi